Upgradeable diamond smart contracts in decentralized autonomous organizations - van Vulpen, Paul; Heijnen, Hidde; Mens, Samuel; Kroon, Thijn; Jansen, Slinger (Frontiers in Blockchain, 2024)
Upgradeable smart contracts allow decentralized autonomous organizations (DAOs) to address bugs, enhance security, and expand functionality post-deployment. The proxy pattern enables smart contract upgradeability but introduces admin-centric governance, where power is concentrated in a single or small number of addresses. This paper explores the potential of decentralized smart contract governance to overcome admin centric governance while achieving flexibility in governing smart contracts. We investigate the Diamond Pattern as a flexible upgradeable contract framework that allows for modular smart contracts. Using the SecureSECO DAO as a case study, we examine how the diamond pattern can be configured for decentralized governance. The used architecture allows DAOs to upgrade smart contracts collectively through community consensus, and the implementation provides proposals, votes, and execution without requiring technical knowledge. The study highlights the benefits of this approach, namely, flexibility in smart contract governance, enhanced modularity, and a single point of interaction for governance. We also discuss limitations and challenges for upgradeable smart contracts such as the decision-making delays and potential vulnerabilities. To encourage adoption of consensus governance, we call for the creation of user-friendly tooling and smart contract facets.